Marine Ecosystems 2015
DOI: 10.1002/9781119116219.ch6
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Vents: Oases at Depth

Abstract: The deep ocean, often called the abyss, covers 66% of the planet. Schematically, it is the marine zone where there is not enough light to allow plants to grow. In fact, the lightened part of the ocean is shallow and does not exceed a few hundred meters; the rest of the ocean can reach much greater depths (11 km in the Mariana Trench) and is in complete darkness except for slight glows of bioluminescence. In the absence of local organic production, the organisms living at depth subsist due to organic matter pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 124 publications
0
3
0
Order By: Relevance
“…The comparison between the control medium and the vitamin-enriched media shows that they do not have a major influence on the growth of Nannochloropsis gaditana, these observations are consistent with the work of De La Noue (1989). Monaco and Prouzet (2014) showed that for the growth of microalgae, the essential macronutrients are carbon, nitrogen, phosphorus. However, micronutrients include iron, cobalt, zinc, manganese and magnesium, which are essential for certain key enzymatic activities and other intracellular functions.…”
Section: Fig 2: Hierarchical Clustering Analysis For Mean Cell Number...mentioning
confidence: 99%
“…The comparison between the control medium and the vitamin-enriched media shows that they do not have a major influence on the growth of Nannochloropsis gaditana, these observations are consistent with the work of De La Noue (1989). Monaco and Prouzet (2014) showed that for the growth of microalgae, the essential macronutrients are carbon, nitrogen, phosphorus. However, micronutrients include iron, cobalt, zinc, manganese and magnesium, which are essential for certain key enzymatic activities and other intracellular functions.…”
Section: Fig 2: Hierarchical Clustering Analysis For Mean Cell Number...mentioning
confidence: 99%
“…After the discovery of hydrothermal vents and their associated communities on the Galapagos rift in the late 1970s, the Pompeii worm Alvinella pompajena Desbruyères and Laubier (1980), was one of the first emblematic species collected from the vent chimney environment following the sampling of a "black smoker" chimney at 21°N on the East Pacific Rise (EPR) (Monaco and Prouzet, 2015). Two morphological types living in close association (syntopy), initially viewed as ontogenic forms, were later found to represent two distinct species, A. pompejana and Alvinella caudata Desbruyères and Laubier (1986) (Jollivet and Hourdez, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Discovered in the late 1970s, hydrothermal vents represent extreme environments with particularly intriguing ecosystems. These habitats, associated with submarine volcanism resulting from the geological activity of oceanic ridges and back-arc basins, offer a large quantity of reduced compounds and energy on which mainly chemosynthetic and highly specialized communities are based (Monaco and Prouzet, 2015). Hydrothermal vents are unstable environments, both in time and space.…”
Section: Introductionmentioning
confidence: 99%